(untitled) (EuroMediterranean Biomedical Journal, 2026)
Today "sports" means both a physical activity and a social pastime. Sociologists and linguists put their attention on language, which offers a large amount of peculiar expressions. Supporters’ fervour and the big fanzines distribution widen up the vocabulary which is build up from borrowing, neologism and semantic stratifications. The result is not a global language but a glocalized product. On the other hand, rhetoric tends to be the same in any articles no matter its origin. The text becomes a fusion between facts (sport reporting and story (which is told as a romance) with different narrative techniques melted together to form a new specialized genre. Looking first to the semantic aspects in football articles, we tried to find out what textual tools are used to describe the sports event focusing on textual emphasis.